β2-Microglobulin is a Novel and Reliable Biomarker for Predicting Ischemic Stroke Recurrence: A Prospective Cohort Study - Hu, Fu-yong; Wu, Wentao; Liu, Qiuwan; Wu, Juncang; Guo, Hualing; Yang, Jing; Wu, Zhuqing; Jiang, Ke; Wang, Guoping; Qian, Yu; Ge, Wei; Qun, Sen (Frontiers in Pharmacology, 2022)
Background and Purpose-Immune and inflammatory mechanisms play key roles in the development and outcome of acute ischemic stroke (AIS). β2-microglobulin (β2M) is the light chain of major histocompatibility complex-1 (MHC-1), which can directly and quickly reflect the immune and inflammatory state of the body. Previous studies have shown a close relationship between β2M and AIS, but its relationship with the recurrence of AIS has not been reported. This study attempted to explore the relationship between β2M and recurrence of AIS. Methods-A single-center AIS cohort involving 135 patients was followed for approximately 26-46 months. Clinical and laboratory data from the patients were collected when hospitalized. The end point was the occurrence of recurrent stroke after patients were discharged. Propensity score matching was used to match cohort groups. Cox regression analysis was used to predict risk factors for recurrent AIS, and receiver operating characteristic curve (ROC) analysis was used to calculate the optimal cutoff value for discriminating recurrence in patients with AIS. Results-The rate of recurrence was 29.6% [95% CI, 21.8%-37.3%] in the follow-up group. Patients with higher levels of serum β2M had a higher risk of stroke recurrence than patients with lower levels of β2M (adjusted hazard ratio, 3.214, [95% CI, 1.557-6.633]; adjusted hazard ratio after matching, 5.831, [95% CI, 2.052-16.572]). A β2M value of 2.31 mg/l was calculated by ROC analysis as the optimal cutoff value for AIS recurrence (area under the curve 0.770, [95% CI, 0.687~0.853]). Conclusions-As a quick responder to the body's immune and inflammatory states, β2M may be a novel and reliable biomarker in predicting AIS recurrence.